2014
DOI: 10.1182/blood-2014-01-553412
|View full text |Cite
|
Sign up to set email alerts
|

FOXP1 directly represses transcription of proapoptotic genes and cooperates with NF-κB to promote survival of human B cells

Abstract: Key Points• FOXP1 directly represses multiple proapoptotic genes in primary mature human B cells and DLBCL cell lines.• FOXP1 cooperates with NF-kB signaling to promote expansion of primary mature human B cells by inhibition of caspase-dependent apoptosis.The forkhead transcription factor FOXP1 is involved in B-cell development and function and is generally regarded as an oncogene in activated B-cell-like subtype of diffuse large B-cell lymphoma (DLBCL) and mucosa-associated lymphoid tissue lymphoma, lymphomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 74 publications
3
77
0
Order By: Relevance
“…MBCs were isolated as previously described. 25 IgA 2 population, using antibodies against CD19, CD27, and PEconjugated antibodies against IgM and IgA (Southern Biotech). Tonsils were obtained from children undergoing routine tonsillectomy as previously described.…”
Section: B-cell Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…MBCs were isolated as previously described. 25 IgA 2 population, using antibodies against CD19, CD27, and PEconjugated antibodies against IgM and IgA (Southern Biotech). Tonsils were obtained from children undergoing routine tonsillectomy as previously described.…”
Section: B-cell Isolationmentioning
confidence: 99%
“…Tonsils were obtained from children undergoing routine tonsillectomy as previously described. 25 Tonsillar B-cell subsets were isolated by FACSAria sorting using an PE-conjugated antibody against CD19 (DAKO), an FITC-conjugated antibody against IgD (Southern Biotech), and an APC-conjugated antibody against CD38 (BD).…”
Section: B-cell Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Another study demonstrated that FOXP1 suppresses apoptosis of DLBCL cells by transcriptional repression of a set of proapoptotic target genes, which includes the BH3-only protein BIK and several p53 regulatory proteins. 19 Here, we have combined a genome-wide search for direct FOXP1 targets using chromatin immunoprecipitation (ChIP) followed by next-generation sequencing and RNA interference with functional screening for biologically relevant target genes to identify novel tumor suppressor proteins in FOXP1-positive DLBCL. We provide evidence that the repressed FOXP1 target sphingosine-1-phosphate receptor 2 (S1PR2) has robust tumor suppressive activity in DLBCL cells in vitro and in vivo and represents an excellent prognostic biomarker that, either alone or in combination with FOXP1 expression, accurately predicts survival of ABC DLBCL patients.…”
Section: Introductionmentioning
confidence: 99%
“…32 Direct FOXP1 target genes, including PAX5, PRDM1, and POU2F1, support a functional role in the GC reaction. 32 Recent studies have provided insight into FOXP1 function in DLBCL cells, indicating contributions to proliferation, 33 inhibition of apoptosis to compliment NF-kB-dependent regulation of proliferation, 34 and Wnt signaling. 25 However, further understanding of FOXP1 isoform expression and functionality is required to pursue emerging evidence indicating that FOXP1 L and FOXP1 S proteins have distinct functions.…”
mentioning
confidence: 99%